INTERPRETATION OF THE CONCEPT OF "PRECEDENT" IN MODERN LINGUISTICS - B.Kh. Abdulkhaeva (Western European Studies, 2024)
In this article, we consider the interpretation of the concept of "precedent" in the modern Russian language, provides an overview of scientific works covering various aspects of precedent units, describes and characterizes thematic groups of precedent phenomena
Keywords: precedent text; precedent statement; precedent name; precedent situation